(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article analyzes the role and relevance of biophysics in modern medicine from a scientific point of view. Biophysics, as a science that studies the functioning of living systems based on physical laws, plays an important role in diagnostics, therapy, medical technologies and biotechnology. The study examines the application of biophysics in the areas of molecular medicine, biomedical engineering, medical imaging, bioelectricity and nanophysics. The article sheds light on the importance of biophysics as a fundamental science that shapes the medicine of the future on a scientific basis.